1988
DOI: 10.1002/jcp.1041370322
|View full text |Cite
|
Sign up to set email alerts
|

Wheat germ agglutinin inhibits thrombin‐induced rises in cytosolic free calcium and prostacyclin synthesis by human umbilical vein endothelial cells

Abstract: To characterize the endothelial cell surface membrane glycoproteins that mediate thrombin stimulation of PGI2 synthesis by human umbilical vein endothelial cells (HUVEC), HUVEC were stimulated with thrombin in the presence or absence of different lectins. Of the lectins tested, only wheat germ agglutinin (WGA) inhibited thrombin-induced rises in cytosolic free calcium [( Ca2+]i), measured using Quin 2-loaded HUVEC and PGI2 production measured by radioimmunoassay. However, WGA by itself had no influence on base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The effect of WGA is therefore consistent with many other endothelium-dependent vasodilators and suggests the relaxation is due to the release of EDRF (Furchgott, 1984). The relaxation to WGA was reversed by N-acetyl glucosamine which is specific for WGA recognition (Grulich-Henn et al, 1988). This sugar was ineffective against acetylcholine-induced relaxation.…”
supporting
confidence: 49%
See 1 more Smart Citation
“…The effect of WGA is therefore consistent with many other endothelium-dependent vasodilators and suggests the relaxation is due to the release of EDRF (Furchgott, 1984). The relaxation to WGA was reversed by N-acetyl glucosamine which is specific for WGA recognition (Grulich-Henn et al, 1988). This sugar was ineffective against acetylcholine-induced relaxation.…”
supporting
confidence: 49%
“…Lectins have the ability to bind to specific saccharide groups of glycoproteins and this binding can be reversed and blocked by specific sugars (Grulich-Henn et al, 1988). Some lectins have been used to label specifically the vascular endothelial cells without labelling the underlying smooth muscle cells (Raub et al, 1990).…”
mentioning
confidence: 99%
“…Lectins can interact with specific saccharide groups of glycoproteins to influence diverse biological processes, such as cell-to-cell signalling, host defence and cell differentiation, although often their precise roles remain poorly understood (Van Damme et al 1998;Beisel et al 1999;Assreuy et al 2003). Such glycoprotein binding can be blocked by specific sugars inhibiting function (Grulich-Henn et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Lectins have the ability to bind to saccharide groups of glycoproteins with this binding being reversed by specific sugars (Grulich-Henn et al, 1988) and have recently been shown to be important in mediating cell to cell interactions by regulating biological processes in living organisms (Sharon & Lis, 1989). The characterization of cell surface glycoproteins including growth factor receptors (Sinnett-Smith et al, 1988), and cell adhesion molecules on endothelial cells (Walz et al, 1990) have also used the unique properties of different lectins.…”
Section: Introductionmentioning
confidence: 99%
“…In cultured endothelial cells, the stimulation of the same receptors causes a coupled release of EDRF and prostacyclin (PGI2) which results in vasodilatation (De Nucci et al, 1988). Thrombin stimulates prostacyclin (PGI2) synthesis in human umbilical vein endothelial cells (HUVEC) (Weksler et al, 1978) and it has been shown that wheat germ agglutinin (WGA) blocks thrombin-induced stimulation of [Ca2+]i, [3H]-arachidonate release, and prostacyclin production in cultured HUVECs (Grulich-Henn et al, 1988). We have suggested that, in the rabbit aorta, WGA binds to a receptor or a cell surface glycoprotein which, via the release of EDRF from the endothelial cell, causes smooth muscle relaxation (Kleha et al, 1991).…”
Section: Introductionmentioning
confidence: 99%